PENDAMPINGAN KESIAPAN PBM DAN MODEL PEMBALAJARAN PBL DI ERA NEW NORMAL BAGI GURU-GURU DI SMA BAITURRAMAH PADANG - Yenni Melia; Erningsih; Hefni; Irwan (Bajang Institute, 2021)
This article aims to conduct a PBL model mentoring program and readiness in carrying out the teaching and learning process in the new normal era. The program implemented at Baiturrahmah High School is a form of ignorance and collaboration of the Sociology education study program with sustainable stakeholders. The implementation method starts from procedures and data collection on program implementation, provides assistance to increase teacher pedagogic competence in implementing learning models that are in accordance with the COVID-19 conditions, builds cooperative relationships between partners and education offices at the district and provincial levels and conducts evaluation designs. The results show that in the era of the covid-19 pandemic, it leads teachers and schools to have preparation in implementing learning. This is a form of knowledge transfer. Transfer of knowledge in the new normal era, the teacher still acts as a facilitator in the implementation of the teaching and learning process. learning starts from the beginning of class, learning materials and models, so that the material provided can be reached by students